“Sorry, my mind just blew up, gotta go home.” Embracing Finnish weird and Arctic hysteria in the Finnish comic Fok_it. - Santoo, Laura (Studia Scandinavica, 2024)
This article offers an overview of a popular Finnish internet and newspaper comic, Fok_it, aimingto analyse its characteristic features, mainly how concepts such as “Arctic hysteria” and “Finnishweird” are represented in it. The genres are usually used in a literary context (when referringto novels and short stories), yet rarely when describing comics or graphic novels. Therefore,the aim is to explore if and how the above-mentioned concepts are shown in the selected comicand how well they could be applied to comics in general.